Urban planning and road traffic: ideas of Alker Tripp in the USSR (Ciudades, 2018)
The massive use of automobiles in Europe at the beginning of the 20th century caused a traffic problem, and with it, the need to rethink urban planning methods. In 1943 in London Alker Tripp published a relevant book where he approached important topics such as the organization of traffic and its relationship with the city. During the post-war period in the context of the establishment of the concept of road traffic in the USSR, the book aroused great interest, and was quickly translated into Russian. As a result, A. Tripp’s ideas influenced Soviet urban planning theory in the 1950s and 1960s
Keywords: urban planning; road traffic; automobile; Alker Tripp; USSR